Atomically thin photoanode of InSe/graphene heterostructure - Haihong Zheng (Nature Portfolio, 2021)
Achieving efficient photoelectrochemical cells requires insights into the ion kinetics at the surface of photoelectrode. Here, the authors show a new platform for investigating strong coupling between hydroxide ions and surface charge carriers by using monolayer InSe as the anode with high photocurrent density.